2014
DOI: 10.4236/wjcd.2014.44026
|View full text |Cite
|
Sign up to set email alerts
|

Associations of High Density Lipoprotein Cholesterol and Framingham Cardiovascular Risk with Diabetic Retinopathy in African Type 2 Diabetics

Abstract: Objectives: To assess the associations of high density lipoprotein cholesterol (HDL-C) and Framingham cardiovascular (CVD) with diabetic retinopathy (DR). Methods: A cross-sectional study of random sample of 200 T2DM Central Africans. Sociobiographical, laboratory and eye examination main outcome measures were investigated using Tertiles of HDL-C (stratification = lowest < 40 mg/dL, normal or interdemiate = 40 -74.9 mg/dL, highest ≥ 75 mg/dL) and Framingham risk stratification (<10% and ≥10%) by logistic regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The follow-up study regarding the association of HDL-C and incidence was very limited. But a crossectional survey in Democratic Republic of Congo revealed the significant U-shaped relationship between DR rates and HDL-C. 50 In another observational study, a modest association was found for higher levels of HDL-C and decreased prevalence of proliferative DR. 51 The reason could be HDL-C maintains the endothelial cells, and in doing so, prevents atherosclerosis, which is a pathological hallmark of microvascular complications of DM. 52 However, various studies showed insignificant association between DR and HDL-C. 3 , 48 , 53 Unlike the results of our study, findings from “NO BLIND Study Group” reported the novel association between high HDL-C and DR. 54 The contribution of high HDL-C to the pathogenesis of DR is still not clear and the explanation of this association is beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 97%
“…The follow-up study regarding the association of HDL-C and incidence was very limited. But a crossectional survey in Democratic Republic of Congo revealed the significant U-shaped relationship between DR rates and HDL-C. 50 In another observational study, a modest association was found for higher levels of HDL-C and decreased prevalence of proliferative DR. 51 The reason could be HDL-C maintains the endothelial cells, and in doing so, prevents atherosclerosis, which is a pathological hallmark of microvascular complications of DM. 52 However, various studies showed insignificant association between DR and HDL-C. 3 , 48 , 53 Unlike the results of our study, findings from “NO BLIND Study Group” reported the novel association between high HDL-C and DR. 54 The contribution of high HDL-C to the pathogenesis of DR is still not clear and the explanation of this association is beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 97%
“…With the increasing levels of sarcosine, and GlyT‐1 was inhibited, high glycine levels in the synaptic cleft will decrease the expression of NMDARs, 28 especially the expression of NR2B‐containing NMADR subunit 29,30 . Therefore, sarcosine can act as a NR2B antagonist, 36 which may reduce NR2B‐mediated neurotoxicity, apoptosis and cell death, and activate NR2A‐mediated cell survival signalling. One study suggests that inhibition of the NR2B subunit could be a potential therapeutic strategy for some retinal diseases, including retinal ischaemia, DR and glaucoma 34 …”
Section: Discussionmentioning
confidence: 99%
“…HbA1c is modified hemoglobin, with glucose linked to the N-terminal valine of the beta chain [9] . It is made in vivo by the non-enzymatic attachment of glucose to hemoglobin [10] .…”
Section: Discussionmentioning
confidence: 99%